Resistance in Public Spaces: Questions of Distinction, Duration, and Expansion. (May 2017) - Frers, Lars; Meier, Lars
What are the limits of resistance in public spaces? Academic representations of acts of resistance often exclusively look at the acts themselves, focusing on performers or participants, but neglecting passers-by. How do these passers-by connect (or not) to these acts and their aesthetics? What about after the action is over and the participants have left? What about effects at sites distant from where the practices of resistance took place? This article uses the works of Michel de Certeau, Pierre Bourdieu, and Jacques Rancière to discuss the restrictions and the potential resistance in public spaces. We investigate the limitations of everyday practices of resistance in public spaces and suggest that future research can better understand the limits of practices of resistance by taking into account three distinct aspects: distinction, duration, and extension. We use Rancière's understanding of aesthetics and the sensible to link accounts of resistance that focus on political subjectivities and those that focus on actual practices of resistance.